Revolution in abortion care? Perspectives of key informants on the importance of abortion method choice in the era of telemedicine - Katy Footman (Sexual and Reproductive Health Matters)
Patient choice of medical or surgical abortion is a standard of quality abortion care, but the choice of surgical abortion is constrained in England and Wales, particularly since the COVID-19 pandemic and introduction of telemedicine. This qualitative study explored the perspectives of abortion service providers, managers, and funders on the need to offer a choice of methods within early gestation abortion services in England and Wales. Twenty-seven key informant interviews were conducted between August and November 2021, and framework analysis methods were used. Participants presented arguments both for and against offering method choice. Most participants felt that it was important to maintain choice, although they recognised that medical abortion suits most patients, that both methods are very safe and acceptable, and that the priority for abortion services is to maintain timely access to respectful care. Their arguments related to practicalities around patient needs, the risk of reinforcing inequalities in access to patient-centred care, potential impacts on patients and providers, comparisons to other services, costs, and moral issues. Participants argued that constraining choice has a greater impact on those who are less able to advocate for themselves and there were concerns that patients may feel stigmatised or isolated when unable to choose their preferred method. In conclusion, although medical abortion suits most patients, this study highlights arguments for maintaining the option of surgical abortion in the era of telemedicine. More nuanced discussion of the potential benefits and impacts of self-management of medical abortion is needed.